Mendialogkan Hakikat Hukum dan Keadilan Pada Berbagai Aliran Pemikiran Hukum dalam Novel Les Miserables - Helmi Kasim (The Constitutional Court of the Republic of Indonesia, 2020)
Justice should be clearly presented in the wording of written law since it will serve as a basis by law enforcement officer and judges in adjudicating cases. The spirit of justice that is contined in the written law should also inspire the way law is enforced and decision made. This paper tries to reflect the essence of justice and law through various plots and characters in Victor Hugo’s novel Les Miserable by looking at it from the perspective of various schools of legal thought. The reflection made shows that a legal event can be studied using various perspectives based on schools of thought in legal science. In the analysis, natural law schools of thought, positivism and feminist jurisprudence were used. Dialoguing these various schools of thought leads to a perspective on how law and justice should be perceived and then expressed normatively before being applied to society.